Terror, leisure and consumption : spaces for harm in a post-crash era - McRae, Leanne (Emerald studies in deviant leisure., 2018)
This book uses a series of case studies from the 'wave ofterror across Europe' to rethink the relationships between harm, crime, deviance, leisure and capitalism.